1987
DOI: 10.1159/000199425
|View full text |Cite
|
Sign up to set email alerts
|

Sulfation of Glycolipids by Human Gastric Mucosa in Disease

Abstract: The activity levels of sulfotransferase enzymes involved in the transfer of sulfate from 3’-phosphoadenosine 5’-phosphosulfate to mucosal membrane and mucus gel glycolipids were studied in fundic and antral mucosal biopsies of patients with severe and chronic gastritis, gastric atrophy, gastric ulcer, and gastric cancer. With sulfotransferase which catalyzes the sulfation of mucus triglucosyl glyceroglucolipid increase in enzyme activity over the control was observed in patients with chronic and severe gastrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Therefore, it is suggested that sulfatide plays a role in mucosal protection. 31) In the case of scirrhous gastric cancer, the molar ratio of sulfatides to GM 3 was extremely low (data not shown). We speculate that sulfatides in scirrhous gastric cancer tissues originated from residual normal gastric mucosa under which scirrhous cancer cells invaded.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, it is suggested that sulfatide plays a role in mucosal protection. 31) In the case of scirrhous gastric cancer, the molar ratio of sulfatides to GM 3 was extremely low (data not shown). We speculate that sulfatides in scirrhous gastric cancer tissues originated from residual normal gastric mucosa under which scirrhous cancer cells invaded.…”
Section: Discussionmentioning
confidence: 91%